Energetics and biomechanics of uphill, downhill and level running in highly-cushioned carbon fiber midsole plated shoes - Hunter, I.; Bradshaw, C.; McLeod, A.; Ward, J.; Standifird, T. (Journal of Sports Science & Medicine, 2022)
Road-racing shoes recently experienced major changes. In the recent past, lightweight, thin midsole shoes were thought to help runners maximize their performance. But, in 2017, Nike released the Vaporfly shoe which transformed the thinking about racing shoe design. Incorporating a curved carbon fiber plate embedded in a thick, compliant and resilient midsole resulted in a reduced metabolic cost across a range of running speeds. We hypothesized the new style of shoes would be less effective uphill than downhill due to the larger ground reaction forces and hence greater elastic energy storage in the shoe during downhill running. Eighteen runners completed two days of testing, each comprising two trials of two shoe models (Saucony Endorphin Pro (EP) and Type A) and three grade conditions (uphill, level and downhill), i.e. 12 trials per day. Oxygen uptake, ground reaction forces, and lower-body kinematics were captured during each condition. Comparisons of the percent metabolic benefit were made between shoes for each grade. Stride rate, ground time, peak vertical force, and flight time were regressed with the percent metabolic benefit of the EP over the Type A shoe across grades. Metabolic benefits of the Endorphin Pro were similar across the three grade conditions (p = 0.778). No significant correlations were observed between how much benefit one runner got over another specific to grade. The new style of road-racing shoes effectively decreases metabolic cost equally across grades. Differences in running mechanics between runners did not explain greater individual metabolic benefits between shoe conditions during uphill or downhill running.